2016
DOI: 10.2147/jir.s117590
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced butyrylcholinesterase activity is an early indicator of trauma-induced acute systemic inflammatory response

Abstract: PurposeEarly diagnosis of systemic inflammatory response syndrome is fundamentally important for an effective and a goal-directed therapy. Various inflammation biomarkers have been used in clinical and experimental practice. However, a definitive diagnostic tool for an early detection of systemic inflammation remains to be identified. Acetylcholine (Ach) has been shown to play an important role in the inflammatory response. Serum cholinesterase (butyrylcholinesterase [BChE]) is the major Ach hydrolyzing enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
4
28
2
Order By: Relevance
“…The optimal cutoff value for the 90-day survival compares to the previously described BChE levels, observed upon the onset of the severe systemic inflammation [ 14 ]. Our previous study showed even stronger reduction of the normalized BChE activity upon systemic inflammation than nonnormalised data [ 21 ]; however, we did not observe this effect in the present study. Probable reason could be that the exact time point of the clinical diagnosis of the sepsis (and the time point of the initial BChE measurement) differed from the actual time point of the primary inflammation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The optimal cutoff value for the 90-day survival compares to the previously described BChE levels, observed upon the onset of the severe systemic inflammation [ 14 ]. Our previous study showed even stronger reduction of the normalized BChE activity upon systemic inflammation than nonnormalised data [ 21 ]; however, we did not observe this effect in the present study. Probable reason could be that the exact time point of the clinical diagnosis of the sepsis (and the time point of the initial BChE measurement) differed from the actual time point of the primary inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with our previous studies, the reduction in BChE activity was observed as early as 1-2 hours following the inflammatory onset [ 21 ]. Moreover, a sustained BChE activity reduction, observed in nonsurviving patients, represents a novel red flag warning indicator in the critical care setting, allowing simple and rapid detection of the high-risk septic patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, some samples were refrigerated before analysis, thereby potentially altering the measured enzyme activity. Zivkovic et al , however, have also identified a reduced BChE activity following surgery 34. They suggested a cholinergic modulation of the inflammatory response that is independent of POD.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence has shown that perturbations in BChE activity are associated with diseases with an inflammatory component (Darvesh et al., ). For example, serum BChE activity levels are reduced in sterile inflammatory responses to surgery and in response to traumatic injury (Zivkovic, Bender, Brenner, Hofer, & Schmidt, ; Zivkovic et al., ). Moreover, genetic variations in BChE have been associated with autoimmune diseases such as arthritis and multiple sclerosis (Reale et al., ; Shahmohamadnejad et al., ).…”
Section: Discussionmentioning
confidence: 99%